THE CONTENT ANALYSIS OF BAHASA INGGRIS TEXTBOOK FOR SENIOR HIGH SCHOOL GRADE X PUBLISHED BY KEMENDIKBUD 2014 - Rut Glory Dilla; Indah - Damayanti; Gita Mutiara Hati (Journal of English Education and Teaching, 2017)
The design of this research was descriptive quantitative. It aimed to find out the category of material and task in Bahasa Inggris Textbook for Senior High School published by Kemendikbud 2014. The subject of this study was textbook for grade tenth, consisting of 2 books (first semester and second semester) which each book consist of 9 chapters which were made up 268 materials and tasks. The data was collected by using observation checklist that proposed by Permendikbud number 08 2016 and some experts (Cunningsworth (1995), Celce-Murcia (1979), Wahab (2013)). The result showed that the materials and tasks which divided into 4 aspects; material aspect, linguistic aspect, material presentation aspect and graph aspect showed the different result. The material aspect was categorized into poor category while the others were categorized into good category. Therefore this book can be categorized into good category. In language skills (listening skill, speaking skill, reading skill and writing skill) also showed the different result. The listening skill showed low percentage in good category while the others skill showed high percentage in good category. Consequently, it can be concluded that language skills in this book was not balance.